Adverse Drug Reaction Monitoring in a Tertiary Level Referral Hospital, Kerala - C, Dilip; M M, Lisa; R, Saraswathi.; R, Divya (Indian Journal of Pharmacy Practice)
This was a prospective spontaneous reporting study conducted for a period of one year, to assess the Causality, level of severity, predictability, and preventability of reported ADRs in tertiary level referral hospital. Clinical pharmacist prompted the clinicians with personal reminders and leaflets to report more ADRs.During the study period a total of 44 ADR reports were received from various departments of the hospital. We observed male 30(71.428%) predominance over female 12(28.571%)) from our study. Among the age groups, Geriatric patients 17(40.476%) reported more number of ADRs, compared to adults 22(52.3809%) and children 3(7.14285%). Maximum number of ADRs came from General Medicine department 27(27.2727%). Multiple drug therapy 18(42.857%) and intercurrent diseases 13(30.952%) were the most prominent predisposing factors of ADRs seen in our hospital. Causality assessment of suspected drugs was assessed using Naranjo scale. According to Naranjo scale most of the reported ADRs were found to be probable 22(50%) followed by possible 18(40.909%) and definite 4(9.0909%). The severities of the reactions were done using Hart Wig Scale. Majority of the reactions were moderate 25(56.818%).Withdrawal of the drug 30(68.188 %) was the main line of the management of the adverse drug reactions in the present study. Adverse drug reactions are an inevitable risk factors associated with the use of modern medicines. However careful attention to dosage, age and renal function can minimise the risk of developing ADRs in many patients. Our study shows that most of the developed ADRs during hospital stays were managed by withdrawing the offending drug and specific treatment. In this pharmacist, physician, nurses, patients and patient's volunteers must help in reporting ADRs If this culture is adopted and practiced well, ADRs can be minimised and good quality of life can be provided to the patients.
Keywords: Adverse drug reaction; severity; causality assessment; clinical pharmacist